2020
DOI: 10.1016/j.celrep.2020.108339
|View full text |Cite
|
Sign up to set email alerts
|

HSV-1 and Zika Virus but Not SARS-CoV-2 Replicate in the Human Cornea and Are Restricted by Corneal Type III Interferon

Abstract: Here, we report our studies of immune-mediated regulation of Zika virus (ZIKV), herpes simplex virus 1 (HSV-1), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the human cornea. We find that ZIKV can be transmitted via corneal transplantation in mice. However, in human corneal explants, we report that ZIKV does not replicate efficiently and that SARS-CoV-2 does not replicate at all. Additionally, we demonstrate that type III interferon (IFN-λ) and its receptor (IFNλR1) are express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 32 publications
4
61
0
Order By: Relevance
“…In terms of replication on the ocular surface, adenoviruses and the herpes simplex virus 1 (HSV-1) are well known to replicate efficiently on the ocular surface [ 136 , 137 ]. In virus-infected cells, double-stranded RNA, which is produced in the cytoplasm by viral replication, acts as an inducer to induce the expression of type I and type III IFNs and IFN-stimulated genes (ISGs), resulting in intracellular antiviral activity [ 136 , 138 , 139 , 140 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of replication on the ocular surface, adenoviruses and the herpes simplex virus 1 (HSV-1) are well known to replicate efficiently on the ocular surface [ 136 , 137 ]. In virus-infected cells, double-stranded RNA, which is produced in the cytoplasm by viral replication, acts as an inducer to induce the expression of type I and type III IFNs and IFN-stimulated genes (ISGs), resulting in intracellular antiviral activity [ 136 , 138 , 139 , 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…In virus-infected cells, double-stranded RNA, which is produced in the cytoplasm by viral replication, acts as an inducer to induce the expression of type I and type III IFNs and IFN-stimulated genes (ISGs), resulting in intracellular antiviral activity [ 136 , 138 , 139 , 140 ]. Blockage of the IFN gamma (known as type III interferon) receptor (IFNgR1) increased susceptibility of the HSV-1 virus; however, interestingly SARS-CoV-2 did not replicate on the cornea [ 137 ], suggesting that SARS-CoV-2 infection is mediated by pathways other than IFNgR1 signaling, leading to delay the innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The type III IFN system protects barriers (61), including the female reproductive tract in Zika (62). Recent work has identified Type III IFN signaling on the ocular surface, with corneal epithelium also expressing both subunits of IFNlR1 (63). Expression of type III IFNs and IFNR1l is consistent with FIGURE 4 | Network of interactions between differentially expressed genes and the first-order interactors of these genes or their encoded products in ZIKV-infected human iris pigment epithelial cell isolates from 20 individual donors.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that conjunctival ACE-2 receptors have very limited role in transmission of the disease [23]. The study done by JJ Miner, DJ Platt, CM Ghaznavi et al in November 2020 showed that SARSCoV-2 virus do not replicate in human corneal explants [24]. They showed that infection of corneal tissue was extremely rare.…”
Section: Discussionmentioning
confidence: 99%